2023
DOI: 10.3390/antiox12111933
|View full text |Cite
|
Sign up to set email alerts
|

XBP1 Modulates the Aging Cardiorenal System by Regulating Oxidative Stress

Ji Zhang,
Yuanyuan Zhao,
Nianqiao Gong

Abstract: X-box binding protein 1 (XBP1) is a unique basic-region leucine zipper (bZIP) transcription factor. Over recent years, the powerful biological functions of XBP1 in oxidative stress have been gradually revealed. When the redox balance remains undisturbed, oxidative stress plays a role in physiological adaptations and signal transduction. However, during the aging process, increased cellular senescence and reduced levels of endogenous antioxidants cause an oxidative imbalance in the cardiorenal system. Recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 163 publications
0
1
0
Order By: Relevance
“…Therefore, we further investigated a canonical UPR pathway (the IRE1-XBP1 pathway) previously implicated in IFN induction and re-dox regulation 27,49 . We confirmed that inhibiting the XBP1 transcription factor with either small interfering RNA (siRNA) or the IRE1 endonuclease inhibitor 4μ8c (Figure S3) blocked ER stress-induced IFNB1 expression (Figure 3B, 3C) 27,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we further investigated a canonical UPR pathway (the IRE1-XBP1 pathway) previously implicated in IFN induction and re-dox regulation 27,49 . We confirmed that inhibiting the XBP1 transcription factor with either small interfering RNA (siRNA) or the IRE1 endonuclease inhibitor 4μ8c (Figure S3) blocked ER stress-induced IFNB1 expression (Figure 3B, 3C) 27,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we further investigated a canonical UPR pathway (the IRE1-XBP1 pathway) previously implicated in IFN induction and re-dox regulation ( 27 , 49 ). We confirmed that inhibiting the XBP1 transcription factor with either small interfering RNA (siRNA) or the IRE1 endonuclease inhibitor 4μ8c ( Supplementary Figure S3 ) blocked ER stress-induced IFNB1 expression ( Figures 3B, C ) ( 27 , 50 ).…”
Section: Resultsmentioning
confidence: 99%